Dermatan sulfate oligosaccharides having reducing end 2, 5-anhydro-d-talose inhibit bovine testicular hyaluronidase activity. (1st September 2019) - Kakizaki, Ikuko; Koizumi, Hideyo; Kobayashi, Takashi; Nakamura, Toshiya; Majima, Mitsuo
Abstract: Dermatan sulfate oligosaccharides having reducing end 2, 5-anhydro-d -talose were prepared by partial N -deacetylation of dermatan sulfate polysaccharide with hydrazine followed by deamination with nitrous acid, and the effect of these oligosaccharides on the activity of bovine testicular hyaluronidase was investigated. Hydrolysis activity and transglycosylation activity of this enzyme were assessed in an independent reaction system by analyzing the products by HPLC. Dermatan sulfate oligosaccharides inhibited hyaluronan hydrolysis by bovine testicular hyaluronidase. Kinetic analysis of the hydrolysis reaction revealed that the inhibition mode by dermatan sulfate oligosaccharides was as competitive as that previously shown by chondroitin sulfate oligosaccharides. Transglycosylation of hyaluronan by bovine testicular hyaluronidase, as a reverse reaction of hydrolysis of hyaluronan, was also inhibited. These inhibitory effects were dependent on the dose and sulfation degree of dermatan sulfate. Graphical abstract: Image 1 Highlights: Oligosaccharides having dermatan sulfate (DS) structure were chemically prepared. DS oligosaccharides inhibited hyaluronan hydrolysis by testicular hyaluronidase. The inhibition mode by the DS oligosaccharides on the hydrolysis was competitive. Transglycosylation by hyaluronidase was also inhibited by the DS oligosaccharides. Inhibitions were in a dose dependent and DS sulfation degree dependent manner.